Associations of abdominal obesity indexes with hypertension in elderly physical examinees in Zhongshan city: a cross-sectional analysis - Xiaoyan FENG; Junyi WANG; Shan WU; Zhihao WANG; Lürong LI; Jilong HUANG; Qingsong CHEN; Tianran SHEN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the relationship between abdominal obesity index and hypertension among the elderly in Zhongshan city for the prevention and control of hypertension. MethodsThe data of the analysis were from 8 318 residents aged ≥ 65 years and participating in free physical examination project during June - September 2020 in a town and a district of Zhongshan city, Guangdong province. Multivariate logistic regression model was used to analyze the relationship between abdominal obesity indexes and hypertension among the residents; the abdominal obesity indexes included neck circumference (NC), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), lipid accumulation product (LAP), and China visceral obesity index (CVAI). The dose-response correlation between NC and the risk of hypertension was analyzed with restricted cubic splines. ResultsThe observed prevalence rate of hypertension among the elderly physical examinees was 45.5% (44.4% in the males and 46.3% in the females). Compared to those in the male and female non-hypertensives, significantly higher mean values of NC (37.29 ± 2.83 cm vs. 36.41 ± 2.82 cm and 33.91 ± 2.67 cm vs. 33.04 ± 2.55 cm), WC (87.90 ± 9.51 cm vs. 84.40 ± 9.59 cm and 86.52 ± 9.48 cm vs. 83.24 ± 9.50 cm), WHR (0.93 ± 0.07 vs. 91 ± 0.07 and 0.91 ± 0.07 vs. 0.90 ± 0.07), WHtR (0.54 ± 0.06 vs. 0.52 ± 0.06 and 0.57 ± 0.06 vs. 0.55 ± 0.06), LAP (43.00 ± 38.70 vs. 32.54 ± 31.22 and 46.98 ± 39.47 vs. 58.08 ± 46.96), and CVAI (116.19 ± 42.01 vs. 98.42 ± 42.94 and 133.18 ± 30.78 vs. 119.80 ± 30.25) were measured in the hypertensives (all P < 0.001). After adjusting for age, education, marital status, monthly household income per capita, smoking, alcohol drinking, exercise, salted vegetable consumption habits, body mass index (BMI), fasting blood glucose (FPG), total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C), multivariate logistic regression analysis showed that the risk of hypertension increased in the male elderly with higher NC compared to that in those with the NC of the lowest quartile (third quartile: odds ratio [OR] = 1.314, 95% confidence interval [CI]: 1.029 - 1.676; the highest quartile: OR = 1.512, 95%CI: 1.131 - 2.022) and in the female elderly with higher WHtR compared to that in those with the WHtR of the lowest quartile (second quartile: OR = 1.214, 95%CI: 1.009 - 1.463; third quartile: OR = 1.289, 95%CI: 1.084 - 1.532; the highest quartile: OR = 1.503, 95%CI: 1.223 - 1.846); the analysis also demonstrated that the risk of hypertension decreased in the male elderly with higher WHtR (the second quartile vs. the lowest quartile: OR = 0.636, 95%CI: 0.469 - 0.863). After adjusting for confounding factors mentioned above, the results of restricted cubic spline analysis revealed a linear dose-response relationship between NC and hypertension risk in both the male and the female elderly (χ2 = 94.62 and 128.22, both P < 0.001). ConclusionThere is a positive linear correlation between NC and the risk of hypertension among the elderly in Zhongshan City.